Initial development and production of CO2 in colonies of the leaf-cutting ant Atta sexdens during the claustral foundation - Camargo, R. S. [UNESP]; Silva, E. J. [UNESP]; Forti, L. C. [UNESP]; De Matos, Cao [UNESP] (Universidade Estadual de Feira de Santana, 2016)
Queens in the genus Atta are solely responsible for fungus cultivation and for care of herself and her offspring. Only few studies have investigated their nests in the claustral foundation and it is unknown the production rate of expelled carbon dioxide and/or of oxygen consumption in the initial colonies of leaf-cutting ants. Thus, we have studied the development of 50 initial colonies of Atta sexdens, and production of expelled carbon dioxide under laboratory conditions. The number of eggs was counted one week after nest foundation on the seventh day, the larvae counted on day 28, and the pupae between days 42 and 49. The workers emerged on the 63rd and 70th day. The CO2 concentration increased steeply in the 42nd days (20.60 ± 8.36%) and 49th days (15.37 ± 13.11 %), at 42nd days, and subsequently returned to lower values, for example, 3.35 ± 2.84% at week seven. It is the first record of CO2 emission data in initial nests, in their claustral foundation under laboratory conditions.
Keywords: Egg; Larvae; Nests; Pupae; Social insects